Employing a flexible and low-cost polypyrrole nanotube membrane as an anode to enhance current generation in microbial fuel cells - Loo, Joachim Say Chye (2015)
The flexible and low-cost polypyrrole nanotube membrane is demonstrated as a promising anode in microbial fuel cells, which significantly enhances the extracellular electron transfer between Shewanella oneidensis MR-1 and the electrode, owing to the large active surface area and high electrical conductivity.